2014
DOI: 10.4103/0975-5950.154816
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral cancer and pre-cancerous lesions and the association with numerous risk factors in North India: A hospital based study

Abstract: Background:Oral cancer is one of the most common life-threatening diseases all over the world. Developing countries face several challenges to identify and remove potential risk factors. Chewing tobacco/pan masala is considered to be the most potent risk factor for oral precancerous lesions and oral cancer.Objectives:To investigate the relative occurrence of different oral pre-cancerous lesions and oral cancer in North India and to identify the associated risk factors.Materials and Methods:A hospital-based stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 14 publications
(13 reference statements)
2
30
1
Order By: Relevance
“…These findings in turn are related with traditional risk factors showing presence of malignant and premalignant lesions in older age groups, males, lower socioeconomic strata and adverse oral habits like tobacco-chewing, gutkha or pan-masala use for prolonged periods. 7,18,19 The findings of present study presented the spectrum of premalignant and oral lesions from a rural centre in Lucknow, the profile of premalignant lesions in present study showed a slight variability from a other study conducted in mixed rural-urban population in our city, thus showing that profile of premalignant lesions depends on the environment and level of exposure to different risk factors. Cross-sectional community based studies with inclusion of patients with normal oral mucosa are recommended to measure the weight of different risk factors.…”
Section: Discussionsupporting
confidence: 50%
“…These findings in turn are related with traditional risk factors showing presence of malignant and premalignant lesions in older age groups, males, lower socioeconomic strata and adverse oral habits like tobacco-chewing, gutkha or pan-masala use for prolonged periods. 7,18,19 The findings of present study presented the spectrum of premalignant and oral lesions from a rural centre in Lucknow, the profile of premalignant lesions in present study showed a slight variability from a other study conducted in mixed rural-urban population in our city, thus showing that profile of premalignant lesions depends on the environment and level of exposure to different risk factors. Cross-sectional community based studies with inclusion of patients with normal oral mucosa are recommended to measure the weight of different risk factors.…”
Section: Discussionsupporting
confidence: 50%
“…6 According to the statistics, in 2012 the incidence of oral cancer in India is 53842 in males and 23161 in females. 7 Agrawal S et al Int J Community Med Public Health. 2020 Jan;7 (1): [367][368][369][370][371][372][373][374][375][376] International Journal of Community Medicine and Public Health | January 2020 | Vol 7 | Issue 1 Page 369…”
Section: Epidemiology Of Oral Cancermentioning
confidence: 99%
“…However, the National Cancer Registry Program provides population-based data from a selected network of 28 cancer registries located across the country. 5 Oral cancer is among the top three types of cancers in India. 6 Severe alcoholism, use of tobacco in the form of cigarettes, smokeless tobacco, and betel nut chewing are the most common risk factors for oral cancer.…”
mentioning
confidence: 99%
“…12 Over 5 people in India die every hour everyday because of oral cancer and the same number of people die from cancer in oropharynx and hypopharynx. 5 The health care fraternity, chiefly the dentists, oncologists, ENT specialists and even physicians also have in depth knowledge of oral cancer. However general population remains largely unaware about the oral cancer.…”
mentioning
confidence: 99%